2014
DOI: 10.1111/cas.12486
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II trial of 2‐weekly docetaxel combined with cisplatin plus fluorouracil in metastatic esophageal cancer (JCOG0807)

Abstract: We carried out a phase I/II trial of adding 2-weekly docetaxel to cisplatin plus fluorouracil (CF) therapy (2-weekly DCF regimen) in esophageal cancer patients to investigate its safety and antimetastatic activity. Patients received 2-weekly docetaxel (30 mg/m2 [dose level (DL)1] or 40 mg/m2 [DL2] with a 3 + 3 design in phase I, on days 1 and 15) in combination with fixed-dose CF (80 mg/m2 cisplatin, day 1; 800 mg/m2 fluorouracil, days 1–5) repeated every 4 weeks. The primary endpoint was dose-limiting toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 24 publications
5
54
3
Order By: Relevance
“…13) In Japan, the JCOG conducted sequential clinical trials to improve the survival for patients with ESCC ( Table 1). 2,12,[14][15][16][17][18][19][20][21][22][23][24] The survival benefit of adjuvant chemotherapy in cStage II/III ESCC was investigated in the JCOG8503 study, where adjuvant radiotherapy (50 Gy) was compared with adjuvant chemotherapy consisting of cisplatin (CDDP) and vindesin (VDS). 15) The five year overall survival rate was 44% in the adjuvant radiotherapy group and 42% in the adjuvant chemotherapy group, indicating no difference in overall survival.…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%
“…13) In Japan, the JCOG conducted sequential clinical trials to improve the survival for patients with ESCC ( Table 1). 2,12,[14][15][16][17][18][19][20][21][22][23][24] The survival benefit of adjuvant chemotherapy in cStage II/III ESCC was investigated in the JCOG8503 study, where adjuvant radiotherapy (50 Gy) was compared with adjuvant chemotherapy consisting of cisplatin (CDDP) and vindesin (VDS). 15) The five year overall survival rate was 44% in the adjuvant radiotherapy group and 42% in the adjuvant chemotherapy group, indicating no difference in overall survival.…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%
“…patient background) into account. The number of metastatic sites is also included because it was indicated as a prognostic factor in the previous Phase I/II trial of this study (JCOG0807) (20). .…”
Section: Randomizationmentioning
confidence: 99%
“…We, JEOG, have developed a 2-weekly DCF regimen in which docetaxel is administered twice every 4 weeks (Days 1 and 15). We conducted a Phase I/II trial to determine the recommended dose for Phase II (RDP2) in Phase I and to investigate the safety and efficacy of the 2-weekly DCF regimen for metastatic or recurrent esophageal cancer (JCOG0807) treatment (20). Our study showed that the RDP2 of docetaxel was 30 mg/m , Days 1-5; every 4 weeks) had promising efficacy with a response rate of 62% and a median OS of 11.1 months.…”
Section: Introductionmentioning
confidence: 99%
“…Triplet regimens that add docetaxel to CF (DCF) are reportedly effective in patients with metastatic SCCE [9-14]. In our previous phase II trial of 48 patients with metastatic SCCE, the response rate of a DCF regimen was 62.5%.…”
Section: Introductionmentioning
confidence: 99%